Makers at school L'apprendimento nell'era post-digitale - Gratani, Francesca (Media e tecnologie per la didattica, 2023)
This volume outlines a theoretical background on the Maker Culture and emerging scenarios in educational technologies in the post-digital era. It will present some experiences and case studies based on Maker Education and carried out internationally. Then, it will describe a pilot project recently experimented in Italy to integrate the Maker approach into the primary and lower secondary school curriculum.